Penggunaan Gaya Bahasa Dalam Lirik Lagu ”Alkohol” Karya Sisitipsi - Muhammad Nafis Shiddiq; Zhilan Aulia Firmansyah (International Forum of Researchers and Lecturers, 2023)
The language of song lyrics is often used as a means of expression in music. Lyric language has special characteristics that distinguish it from everyday language, because lyrical language can combine artistic elements such as rhyme, rhythm, and repetition to create sounds and that touch the listener's feelings.The use of lyrical language in songs is very important to convey an emotional or narrative message in a way that is easy for listeners to remember and absorb. Lyrical language can be used to create nuance, describe situations or feelings, and to describe the character or personality of someone or something.Songs can also carry different tones meanings for listeners, depending on how they interpret the lyrical language used. This makes the use of lyrical language a very effective tool for communicating important messages that may be difficult to explain in ordinary words. In the context of popular music, lyrical language can also help in creating an artist's or band's identity, and can be a determining factor in the success of a song or album. For example, strong and memorable song lyrics can help the song become a hit and make the artist or band famous. However, the use of lyrical language in songs can also be controversial. Some lyrics may be considered to contain inappropriate or unethical messages, and may cause controversy or protest from the public.